Вероятность "среза" импульсов тока в контуре емкостного накопителя энергии с вакуумным разрядником - Лютенко, Л.А.; Михайлов, В.М. (Технічна електродинаміка, 2012)
The statistic of arise of interruption current pulses in discharge circuit of magnetic-pulse plant with controlled vacuum discharger to charge voltage and capacity of capacitor bank ratio is obtained. The duration and amplitude of first halfwave of current pulse are changed ranges from 130 μs to 200 μs and from 18 kA to 67 kA. The current rate in going from first half-wave to second half-wave of current pulse is estimated. The intervals of the more probability of arise of interruption current pulses are determined.